Enhancement of sugars recovery from residual strach of sago hampas through retrogradation reaction - Nurul Nakhiah, Rubian (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Sago hampas which contain mostly starch is potentially for production of reducing sugars which able to be used as fermentable sugar. In this study, the yield of reducing sugars from sago hampas after undergo the retrogradation reaction (24 h, 48 h and 72 h) at 4°C was examined. The substrate loading is fixed at 7% (w/v). The retrograded starch was further hydrolysed into reducing sugars utilising liquozyme and spirizyme enzymes. From the result obtained, there is not much different of reducing sugars concentration at different period of retrogradation reaction. However, after 48 h of retrogradation reaction 55.71% of reducing sugar was obtained higher compared to 24 h and 72 h which was 36.60 %, and 48.80 % respectively. This result indicates that the retrogradation reaction can enhance the starch recovery from sago hampas, thus able to increase reducing sugars concentration.